2019
DOI: 10.3390/agronomy9020090
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Body Condition Score in Dairy Cows From Depth Images Using Convolutional Neural Networks, Transfer Learning and Model Ensembling Techniques

Abstract: BCS (Body Condition Score) is a method to estimate body fat reserves and accumulated energy balance of cows, placing estimations (or BCS values) in a scale of 1 to 5. Periodically rating BCS of dairy cows is very important since BCS values are associated with milk production, reproduction, and health of cows. However, in practice, obtaining BCS values is a time-consuming and subjective task performed visually by expert scorers. There have been several efforts to automate BCS of dairy cows by using image analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Until now, there are some research achievements in assessing BCS by machine learning [14,15,16,17], they need the help of veterinarians or experts to score the cows, human empirical rules are the basis for machine learning. In reference [14] and [17], when the image data was acquiring, an expert was arranged to score the BCS of cows in situ. In our study, we made the same arrangement, two veterinary experts were asked to stand beside the milking corridor, and to record the BCS value of each cow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, there are some research achievements in assessing BCS by machine learning [14,15,16,17], they need the help of veterinarians or experts to score the cows, human empirical rules are the basis for machine learning. In reference [14] and [17], when the image data was acquiring, an expert was arranged to score the BCS of cows in situ. In our study, we made the same arrangement, two veterinary experts were asked to stand beside the milking corridor, and to record the BCS value of each cow.…”
Section: Discussionmentioning
confidence: 99%
“…A group of metrics are used to evaluate the performance of models. The following seven important terms that need to be introduced, they are also commonly used in other literature [16,17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments, 1661 cow images in practical experimental environments were collected and analyzed to estimate the body condition score of each cow for the evaluation of the proposed method. The results showed that both accuracy and F1-score of the proposed method were 0.97 [42].…”
Section: Dl-based Image Recognition Techniques For Agronomy Applicationsmentioning
confidence: 97%
“…Three papers on DL-based image recognition techniques for agronomy applications are as follows: (1) "Automatic segmentation and counting of aphid nymphs on leaves using convolutional neural networks," by Chen et al [41]; (2) "Estimating body condition score in dairy cows from depth images using convolutional neural networks, transfer learning, and model ensembling techniques," by Alvarez et al [42]; and (3) "Development of a mushroom growth measurement system applying deep learning for image recognition," by Lu et al [43].…”
Section: Dl-based Image Recognition Techniques For Agronomy Applicationsmentioning
confidence: 99%